Invisible Work and Exclusionary Space: Too Many Challenges for Homeworkers? - Baylina, Mtreia (Hagar: Studies in Society and Culture, 2004)
This article tries to highlight the nature and function of women’s industrial homework in the rural areas of Spain. I place special focus on the space and time of homework, as this type of work is probably the best activity to highlight the complex geographies of production and reproduction and examine how this work challenges the boundaries of "home" and "work." As women make particular and peculiar use of their homes as places of (re)production, home-based activities are an excellent example for demonstrating how the spatial organization of activities is not only a passive expression of existing gender roles and relations, but may also reinforce or weaken these relations. Moreover, homework, as an "invisible" activity, due to the private workplace and its clandestine features, is a great example to show up to which point global processes reinforce social and spatial exclusion.